IMPLEMENTASI PROGRAM BIMBINGAN DAN KONSELING DALAM KURIKULUM 2013 DI SMAN 4 WATAMPONE - SYAHRIL SYAHRIL (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2017)
This research has purpose to know implemnetasi guidance and counseling program in Curriculum 2013. This research is classified as descriptive qualitative research by using pedagogical, psychological, and sociological approach. Implementation of research conducted at SMAN 4 Watampone Kab. Bone. The subjects of the study consisted of 1 leader and 4 counseling and guidance teachers using purposive sampling samples whose number could occasionally increase by using snowball sampling in line with the development of research data needs. Implementation of guidance and counseling in Curriculum 2013 at SMAN 4 Watampone shows that the interest of learners in Curriculum 2013 become a thing of counseling and counseling in various dimensions ranging from philosophy framework to its technical implementation.Keywords: Bimbingan dan konseling dalam kurikulum 2013.